Design and Construction of Sulobaja Village Park, Tobadak District, Central Mamuju Regency, West Sulawesi - Ganies Riza Aristya; Ilham Fauzi; Anthony Yuwono Saputro; Sabrina Salma Jannata; Leoni Yessa Tifani; Zafran Daffa Imanda; Erlangga Aravi Nugroho; Aya Sofia Mulifatul Khoeriyah; Nayla Rasya Nareswari (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
Sulobaja Village is one of the villages located in Tobadak District, Central Mamuju Regency, West Sulawesi Province. The creation of the Sulobaja Village park was motivated by the lack of educative green open space in the village, which can function as a place of recreation as well as a source of learning for the community. The main objective of making this park is to provide green open space that not only beautifies the village environment but also provides educational benefits for residents, especially in the fields of agriculture, environment, and health. The implementation of the Sulobaja Village park started from July 22 to July 28, 2024. The method used in making this park includes several stages, namely designing the Sulobaja Village Park, preparing materials and equipment such as soil, rocks, compost, crops, ornamental plants, and tools such as shovels and angkong. After all materials and equipment are available, the park construction process begins by planting crops and ornamental plants, and building other supporting facilities. The results of the garden include decorations that read “SULOBAJA” as the garden icon, planting of crops equipped with a drip irrigation system, and planting of ornamental plants with mist irrigation to maintain optimal humidity. In addition, the park is also equipped with segregated waste bins to support good waste management programs, as well as information boards containing various educational posters about the environment, agriculture, and health. In conclusion, Sulobaja Village Park has successfully realized a green open space that not only improves the aesthetics of the village but also serves as a medium for education and community empowerment.